Allyl–aryl coupling of allylic carbonates with arylboronic acids catalyzed by palladium nanoparticles in ionic liquid. Issue 11 (18th March 2015) - Xu, Jing; Zhai, Xing; Wu, Xue; Zhang, Yong Jian
Abstract: A practical and greener process for the allyl–aryl coupling of allylic carbonates with arylboronic acids catalyzed by in situ generated palladium nanoparticles (PdNPs) in ionic liquid (IL) has been described. The PdNPs showed high catalytic activity for the coupling reaction in the IL to afford allyl–aryl coupling products in good to high yields with complete regio- and E / Z selectivities. The PdNPs were readily immobilized in the IL phase and the catalyst can be reused several times without significant loss of catalytic activity and stereospecificity. Graphical abstract: